Perancangan Pusat Pagelaran dan Pelatihan Seni Audio Visual (Modern-Tradisional) Dengan Konsep Arsitektur Ekspresionisme di Kec.Umbulharjo, Yogyakarta - Putri, Betaviane Indah; Suryandari, Putri; Kurniasih, Sri (MAESTRO, 2021)
The Design of Modern-Traditional Audio-Visual Art Performance and Training Center With the Concept of Expressionism Architecture is a building with its main function as a means of entertainment to facilitate audio-visual arts performances specifically dance art, drama and opera as well as educational facilities for art performers to practice the audio visual arts. Art is a communication media for human based on experience, feelings and has a beauty that is expressed through a creation. This underlies the reason for applying the architectural concept of expressionism which has the nature of freedom of expression based on the expression of feelings of the heart. Located in the city of Yogyakarta, which is known as the city of students and the city of the arts, it is expected that it will be a means to preserve audio-visual arts, both modern and traditional, and be able to respond to the need for large number of performance facilities for both art performers and the wider community. Keywords: Performance and Training Center, Art, Expressionism Architecture, Yogyakarta.